Física e música: produção, transmissão, percepção e comunicação - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This work arises in the context of rethinking the teaching of Physics in a contextualized and interdisciplinary way for basic education. Thus, it is proposed a material that can be used for didactic purposes to approach the theme "Physics and music: production, transmission, perception and communication", as it was noticed that although music is very present in the students' lives, it is still little explored in the teaching of Natural Sciences/Physics. The general objective is to present the theme Physics and Music using a thematic approach, so that the presented text can serve as a didactic support for the discussion in basic education. As a methodology, bibliographic research was carried out in various sources such as textbooks, articles, course conclusion works, dissertations and theses that are related to the theme. From this survey, a text was prepared that is presented in the results, which has contextualization and interdisciplinarity as fundamental characteristics. The text was designed for high school students, but due to its primarily conceptual character, it can also be used with students at the end of elementary school. In this text, the contents and equations arise as the situations and questions related to the theme are presented and the need to understand them appears in the context, since in Teaching Physics Through Themes (EFAT), the scientific concept is subordinated to the theme. . Finally, we suggest a proposal that the teacher can make use of the text, following the steps of Presentation of the theme, Deepening and Productionevaluation of EFAT. We hope that the material and the proposal will be useful to all teachers who wish to start or continue a process of change in the way of conceiving Physics teaching, prioritizing a thematic approach that meets the current trends in Science Education and the Physics teaching.
Keywords: Física e música; Ensino de física; Acústica; Abordagem temática; CNPQ:: CIÊNCIAS EXATAS E DA TERRA